2021
DOI: 10.1007/s00253-021-11349-0
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of mycobacteria to combat infection diseases: current state and perspectives

Abstract: The spread of multi-drug-resistant bacterial strains causing serious infectious diseases dictates the development of new approaches to combat these diseases. In addition to drug resistance, the important causative agent of tuberculosis (Mycobacterium tuberculosis (Mtb)) is able to persist asymptomatically in individuals for many years, causing latent forms of tuberculosis. In such a dormant state, Mtb cells are also resistant to known antibiotics. In this regard, photodynamic inactivation (PDI) could be an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…These results are in accordance with our previous studies, in which we tested the effect of ALAD-PDI on both Gram-positive and negative bacteria [20,35]. By comparison, previous literature that used different formulations of aminolevulinic acid followed by photodynamic therapy (ala-PDI) showed contradictory results, especially on Gram-negative bacteria [36,37]. It was shown that the increase in reactive oxygen species (ROS) induced by ala-PDI promotes intracellular biopolymer leakage, photocleavage on genomic DNA, cytoplasm denaturing, and envelope injury [38].…”
Section: Resultssupporting
confidence: 91%
“…These results are in accordance with our previous studies, in which we tested the effect of ALAD-PDI on both Gram-positive and negative bacteria [20,35]. By comparison, previous literature that used different formulations of aminolevulinic acid followed by photodynamic therapy (ala-PDI) showed contradictory results, especially on Gram-negative bacteria [36,37]. It was shown that the increase in reactive oxygen species (ROS) induced by ala-PDI promotes intracellular biopolymer leakage, photocleavage on genomic DNA, cytoplasm denaturing, and envelope injury [38].…”
Section: Resultssupporting
confidence: 91%
“…One of the most effective photosensitizers are porphyrins 4 , among which zinc complexes standout 5 11 . Zn–coproporphyrin is considered as a promising compound for PDT of tumors 12 .…”
Section: Introductionmentioning
confidence: 99%
“…17 Nevertheless, there are still problems when performing PDI on skin due to the presence of some substances on the skin surface like divalent ions. [32][33][34] Moreover, the application of a photosensitizer dissolved in pure water is not only impractical but also hampers the important wetting of the bacteria with the photosensitizer solution. Such wetting is important for the maximum proximity of photosensitizers and bacteria, which ensures good accessibility of the bacteria by singlet oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are still problems when performing PDI on skin due to the presence of some substances on the skin surface like divalent ions 32–34 . Moreover, the application of a photosensitizer dissolved in pure water is not only impractical but also hampers the important wetting of the bacteria with the photosensitizer solution.…”
Section: Introductionmentioning
confidence: 99%